The Effectiveness of Digital Learning Media Based on Project Based Learning Assisted by Geogebra Classroom on Mathematics Learning Outcomes of Vocational High School Students - Husnul Khotimah; Amin Harahap; Lily Rohanita Hasibuan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2026)
This research evaluates how Project-Based Learning (PjBL) integrated with GeoGebra Classroom influences the mathematical performance of vocational high school students specifically regarding trigonometry. The investigation employs a quantitative method characterized by a quasi-experimental design with a non-equivalent control group. The subjects of the study included two classes: one experimental class with 34 participants and one control class with 35 participants. The assessment tool utilized was a multiple-choice quiz consisting of 20 questions that underwent validation and reliability checks. Data analysis encompassed both descriptive and inferential statistics. The prerequisite tests conducted involved a normality assessment via the Kolmogorov-Smirnov test and a homogeneity test using the Levene test. The findings from the normality assessment indicated that not all data followed a normal distribution, prompting further analysis with nonparametric methods, specifically the Wilcoxon and Mann-Whitney tests. Additionally, the advancement in academic performance was evaluated through the N-Gain Score. The findings demonstrated a notable distinction between the pretest and posttest scores in both the experimental and control groups. The average N-Gain score for the experimental group was 0.66, categorized as moderate, whereas the control group recorded an average of 0.37, also within the moderate range. The Mann-Whitney test results indicated a significance level of 0.000.